Stabilization of Polypropylene for Rotational Molding Applications - Emaldi, Iñaki; Liauw, Christopher Mark; Potgieter, Herman (Journal of Research Updates in Polymer Science, 2016)
Rotational molding (RM) is a useful process for making large hollow objects. Due to its relatively high toughness and forgiving thermal oxidative degradation behavior, polyethylene is a most widely used material. However, it has too low elastic modulus for some important applications which leads to adaptation of polypropylene (PP) as a RM material. PP requires specially tailored antioxidant (AO) packages if it is to have any chance of surviving the often long (up to ca. 30 minutes) cycle times associated with RM. During the study the addition of the following stabilizers and antioxidants (AO) to the PP copolymer were investigated: a hindered phenolic primary AO, a phosphite secondary AO, a thioester secondary AO and a hindered amine light stabilizer. Synergistic effects between the primary and secondary AOs, as well as optimum heating times, were investigated. During the investigation formulations were prepared by compression molding and bench-scale RM. The combination resulting in the most effective synergism is the hindered phenolic primary antioxidant combined with the phosphite secondary antioxidant. A gel silica controlled release agent for the stabilizers was also investigated but did not yield significant improvements in stabilization.